A Study on the Productivity and Viability of Women-Led Backyard Poultry Systems in Selected Villages of Kilinochchi District, Sri Lanka - Theebagaran, R.; Thatchaneshkanth, S.; Kajaranjan, S.; Vinopavan, K.; Thevathas, S. (University of Jaffna, 2025)
The present study evaluates the performance of women-led backyard poultry (WLBP) systems in four selected villages: Barathipuram (BP), Kirishnapuram (KP), Vivekananda Nagar (VN), and Malayalapuram (MP) in the Kilinochchi District through an integration of backyard poultry best practices through the Farmer Field Business School (FFBS) Approach and village-based savings and credit mechanisms. The detailed data were gathered in January 2025 from 126 WLBP farmers. KP had the highest proportion of WLBP small-scale farmers (33%), followed by BP (24%), VN (23%), and MP (21%). All villages recorded 2,050 hens during the period. In BP, 67% of farmers produced eggs, averaging 284 eggs per farmer, whereas in MP, only 15% produced eggs, with an average of just 83 eggs per producer for the last 3 months. The highest poultry mortality rate was observed in MP at 39%, followed by KP at 25%, BP at 22%, and VN at 15% in the first six months. Additionally, losses in chick numbers are being replaced by traditional hatching methods. Correspondingly, BP recorded the highest average monthly income (LKR 12,000) from egg sales, followed by KP (LKR 9,000), VN (LKR 7,500), and MP (LKR 2,750), excluding their home-level consumption. The established group-based savings and credit initiatives support to development of backyard poultry. They mobilize LKR 1,330,680, alongside recycled loans of LKR 1,033,000. The loan range is LKR 15,000 to 35,000, and the average savings per farmer is LKR 10,560 to date. These differences in management, particularly evident in locally available resources for feeding, healthcare, and record-keeping. The findings suggest that BP farmers and their poultry systems are more effective. It is recommended to refine these practices and develop a replicable backyard poultry model suited for Kilinochchi conditions.
Keywords: Backyard Poultry; Egg Production; Feeding Kilinochchi; Poultry Farming